A Keynesian analysis of Canadian government securities yields - Anupam Das; Tanweer Akram (PSL Quarterly Review, 2020)
Keynes argued that the short-term interest rate is the main driver of the long-term interest rate on government bonds. This paper empirically models the relationship between the short-term interest rate and long-term government securities yields in Canada, after controlling for other important financial variables. The statistical analysis uses high-frequency daily data from 1990 to 2018 to examine the behavioral dynamics of the long-term interest rate. The empirical results show that the actions of the Bank of Canada are key drivers of Canadian government securities yields in the long run, which supports the Keynesian perspective. There is a positive association between long-term bond yields and the Canadian federal government’s net debt to GDP ratio, but the effect is fairly modest. An important implication of these findings is that the Bank of Canada’s actions can have a decisive effect on the long-term interest rate over the long horizon. JEL codes: E43, E50, E60, G10, G12